Efficiency and safety of his bundle pacing in patients with newly-acquired heart failure after long-term right ventricular pacing, results from China mainland. (25th November 2020) - Yiheng, Y.A.N.G; Kexin, W.A.N.G; Yunlong, X.I.A; Yingxue, D.O.N.G
Abstract: Background: Clinical outcomes of his bundle pacing (HBP) lead implantation in patients with pacing induced cardiomyopathy (PICM) are unknown. We aim to investigate the efficiency and safety of HBP upgrade in a single center. Methods and results: Patients with PICM and indication of resynchronization therapy were selected during 2018.1–2019.12. Clinical data including parameters of echocardiographic examination, ECG measurements, New York Heart Association (NYHA) classification were assessed before and after HBP upgrade. HBP upgrade was fulfilled in 38 of 40 (95%) patients. During a mean of 9.36±5.63 months follow-up, 28 patients completed the follow-up of clinical data. The mean age was 67.86±12.85 years and men account for 67.9%. Mean of H-V interval was 56.86±7.11ms. Left ventricular ejection fraction (LVEF) significantly increased from baseline 32.75% to 44.19% (P<0.01). QRS duration decreased from 184.67±27.35 ms at baseline to 123.28±15.82ms with HBP (P<0.01). LVEDD remodeled reversed from 60.85 mm at right ventricular pacing (RVP) implantation to 53.16mm. NYHA functional class improved to 1.96 from 2.64 at baseline during follow-up (P<0.01). Over a median follow-up period of 3.03 (0.9–19.4) months, threshold of his bundle lead decreased from baseline 1.35±0.89mv to 1.2±0.89mv but no significance (P=0.308>0.05). Conclusion: HBP significantly improved echocardiographic measurements and NYHA classification for those with PICM. The threshold of his bundle lead is relatively stable in our follow-up period, reminding that the HBP upgrade is safe and effective for PICM patients. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): This study was supported by grants from Liaoning Clinical Capacity Construction Funding (LNCCC-D-20-2015).